2003
DOI: 10.1890/02-0220
|View full text |Cite
|
Sign up to set email alerts
|

Who Bears the Costs of Interspecific Competition in an Age-Structured Population?

Abstract: Social and density-dependent life history processes may differ according to age and the reproductive history of individuals. Arvicoline rodents have a typical, seasondependent, bimodal, age distribution of breeding individuals within a population. This distribution may influence population fluctuations. In this study, we measured effects of interspecific competition from field voles (Microtus agrestis) on various fitness components of female bank voles (Clethrionomys glareolus) in an age-structured breeding po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 44 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…Gustafsson et al (1980, 1983) assumed lactational anoestrus in a laboratory colony of caged bank vole pairs, since only 2% of females ( n  = 640) conceived during lactation. Meanwhile, in semi-wild experimental bank vole populations in large outdoor enclosures, we observed that 40% of non-gravid, lactating females (Eccard and Ylönen 2003, n  = 39 females) and 9 out of 10 of non-gravid, lactating females (re-analysing data reported in Eccard et al 2017) were conceiving within days after being release to enclosures, while still accompanied by their several days-old litter.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…Gustafsson et al (1980, 1983) assumed lactational anoestrus in a laboratory colony of caged bank vole pairs, since only 2% of females ( n  = 640) conceived during lactation. Meanwhile, in semi-wild experimental bank vole populations in large outdoor enclosures, we observed that 40% of non-gravid, lactating females (Eccard and Ylönen 2003, n  = 39 females) and 9 out of 10 of non-gravid, lactating females (re-analysing data reported in Eccard et al 2017) were conceiving within days after being release to enclosures, while still accompanied by their several days-old litter.…”
Section: Introductionmentioning
confidence: 48%
“…3, Table 2) revealed a general response to the male scents independent of familiarity, which may indicate a general interest in mating and future reproduction among the females. After missing the post-partum oestrus, female bank voles seem to be able to conceive during lactation (re-analysed from Eccard and Ylönen (2003) and Eccard et al (2017), but see Gustafsson et al 1980, 1983) and interaction with male scents and males may trigger a behavioural oestrus, during which females were reported to actively visit males for mating (Klemme et al 2011). In the control treatment, we found a negative correlation between litter size and the total time spent at the scent area, as well as a negative correlation with the longest visit at the scent area (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In late summer, space use of reproducing females, which was initially 828 ± 86 m 2 without competitors, decreased by 33% in the presence of 5–12 field voles (Fig. 1 in Eccard and Ylönen 2002; data from 16 independent populations within 1 year, analyses by age groups in Eccard and Ylönen 2003a, b). In addition, when competitor density increased to different densities, the space use of bank vole females decreased linearly from 870 m 2 without competitors to 330 m 2 in the presence of 30 field voles (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies forcing situations of coexistence of probable competitor species offer a tool to study both mechanisms of competition and density-dependent processes (Eccard and Ylönen 2003a). For a number of years our group has studied competitive interactions over several breeding seasons in a system with two microtine vole species, the bank vole ( Myodes glareolus ) and the field vole ( Mirotus agrestis ) (Eccard and Ylönen 2002, 2003a, b, 2007; Eccard et al 2002). In these studies, we observed that the presence of field voles decreased space use and the survival of bank voles.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, low numbers of over-wintered animals can be found in spring, followed by an increasing population density during the breeding season leading to a density peak in summer, with a subsequent population break down in autumn or winter. In mammals, these patterns are typical for small mammals, for example, bank vole Myodes glareolus: (Eccard & Ylonen, 2003;Koivula, Koskela, Mappes, & Oksanen, 2003) but also for European rabbit Oryctolagus cuniculus (Cowan, 1987). At the same time, many life-history variables are adapted to seasonality (Paul, Zucker, & Schwartz, 2008).…”
Section: Introductionmentioning
confidence: 99%